Zoonotic necrotizing myositis caused by Streptococcus equi subsp. zooepidemicus in a farmer. Issue 1 (December 2017) - Kittang, Bård; Pettersen, Veronika; Oppegaard, Oddvar; Skutlaberg, Dag; Dale, Håvard; Wiker, Harald; Skrede, Steinar
Abstract Background Streptococcus equi subsp.zooepidemicus is a beta-hemolytic group C streptococcus mainly causing infections in domesticated animals. Here we describe the first case of zoonotic necrotizing myositis caused by this bacterium. Case presentation The patient was a 73-year-old, previously healthy farmer with two asymptomatic Shetland ponies in his stable. After close contact with the ponies while feeding them, he rapidly developed erythema of his left thigh and sepsis with multiple organ failure. The clinical course was severe and complicated, requiring repetitive surgical excision of necrotic muscle, treatment with vasopressors, mechanical ventilation and continuous venovenous hemofiltration, along with adjunctive hyperbaric oxygen therapy. The patient was discharged from hospital at day 30, without obvious sequelae. The streptococcal isolate was identified asStreptococcus equi by MALDI-ToF MS, and was later assigned subspecies identification asS. equi subsp.zooepidemicus . Multilocus sequence typing identified the strain as a novel sequence type (ST 364), closely related to types previously identified in horses and cattle. A focused proteomic analysis revealed that the ST 364 expressed putative virulence factors similar to that ofStreptococcus pyogenes, including homologues of the M protein, streptodornases, interleukin 8-protease and proteins involved in the biosynthesis of streptolysin S. Conclusion This case illustrates the zoonotic potential ofS. equi subsp.zooepidemicus and the importance of early clinical recognition, rapid and radical surgical therapy, appropriate antibiotics and adequate supportive measures when necrotizing soft tissue infection is suspected. The expression ofStreptococcus pyogenes -like putative virulence determinants in ST 364 might partially explain the fulminant clinical picture.